The static and dynamic concepts of legal certainty - Iuliia Matvieieva (Наукові записки НаУКМА: Юридичні науки, 2018)
Legal certainty is the main idea for the entire legal system. The degree and manner it is included to positive law varies from system to system, but its implementation in a certain form is important for individual autonomy. Legal certainty has the key role in creating legal methods that form, recognize, and apply the law. At the same time, legal uncertainty cannot and does not have the same leading function as does the Legal certainty. When uncertainty is covered or expected, the rules set back in order of importance; i.e., if we cannot guarantee making the decision according to the law and legal rules, then we at least can guarantee it in accordance with the legal process. Thus, if legal certainty in the legal systems of common law is not ensured by clarity and accessibility of legal statements, it is achieved by applying the similar court decisions, as well as compliance with the rules of due process of law. These rules serve as procedural aspects and principles of court consideration. The Civil law is characterized by regulations and codification. The latter is a systematic and rational streamlining of laws into official codes. Thanks to this codification, the Civil law becomes reachable. It is clear and easy to understand, so any people, owners or consumers reading the codes can find out how the rules of law can be applied towards them. The law is also easily understood, as each rule is formulated with simple and general terms. This results in legal certainty, which is the main advantage for citizens, allowing them to predict the outcome of court proceedings and estimate financial risks in case of a court appeal. Thus, legal certainty in different legal families is provided in different ways; this creates the basis for the allocation of static and dynamic concepts of legal certainty. The static concept is provided by an effective system of codified legislation, which prescribes requirements to the content of the law – it must be fairly clear, understandable and accessible to ordinary people. On the other hand, dynamic concept is based on a flexible and more creative approach to resolving legal disputes and is ensured by the predictability of the judicial system and a significant law-forming role of judges in making decisions.